BAHASA LASALIMU-KAMARU: KAJIAN DIALEKTOLOGI - Firman A. D. (Kantor Bahasa Provinsi Gorontalo, 2017)
The purpose of this reserach is to describe the difference of languageelements of the isolects and elaborated kinship of its inter-dialect status.The Collecting of data was conducted by using interview and listeningmethods by choosing four regions as observation area.An instrument in this study was focused on a list of 200 Swadesh basic vocabularies and 87 additional vocabularies. In analyzing Lasalimu-Kamaru language was used comparative method that was both quantitative and qualitative.Qualitative method trying to describe a gloss phonetically in Lasalimu-Kamaru language based on the location of observation. While the quantitative analysis of determination of Lasalimu-Kamarudialects was done by using the dialectometry method. In clarifying the data analysis, presented some sound correspondence of the dialects. Based on data analysis found that four isolects used as a data research was obtained three isolects had status as dialect, that were Lasalimu, Kamaru, and Kekenauwe-Lawele. Theposition of Kekenauwe and Lawele isolect only show differences as subdialect. Besides, some qualitative evidences show that Lasalimu dialect and Kamaru dialect are closer than Lawele-Kekenauwe dialect.